Conceptualization of Out-of-School Mathematics Education - Mehtap Kuş (Yaşadıkça Eğitim, 2024)
Out-of-school mathematics education is a relatively new domain. This paper examines learning environments in out-of-school mathematics education, where teachers play a role. These environments fall into three major categories: (a) real-life settings (working places, outdoor environments, daily life settings like home), (b) designed learning environments (e.g., museums, libraries, zoos), and (c) outside classroom settings in schools (e.g., school gymnasiums, art studios). This study highlights interchangeable use of “non-formal” and “informal” education by researchers and raises concerns regarding potential conflicts between informal education programs that employ formal approaches and the inherent nature of informal mathematics education. As a solution, this paper proposes using La Belle’s matrix (1982) to analyze current out—of-school mathematics education programs and identify their educational approaches. This contribution will broaden the conceptualization of out-of-school mathematics education and guide future research by examining critical issues.